Complete Genome Sequences of Penicillin-Resistant Bacillus anthracis Strain PCr, Isolated from Bone Powder - Okutani, Akiko; Inoue, Satoshi; Morikawa, Shigeru (Microbiology resource announcements, 2019)
Bacillus anthracis , the etiologic agent of anthrax, is susceptible to beta-lactam antibiotics, but few cases of naturally occurring penicillin-resistant strains have been reported. We report the genome sequence of penicillin-resistant strain Bacillus anthracis PCr, isolated from imported bone powder in 1978 in Japan. Bacillus anthracis , the etiologic agent of anthrax, is susceptible to beta-lactam antibiotics, but few cases of naturally occurring penicillin-resistant strains have been reported. We report the genome sequence of penicillin-resistant strain Bacillus anthracis PCr, isolated from imported bone powder in 1978 in Japan.